2013
DOI: 10.1016/j.cbi.2013.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Connecting glutathione with immune responses to occupational methylene diphenyl diisocyanate exposure

Abstract: Methylene diphenyl diisocyanate (MDI) is among the leading chemical causes of occupational asthma world-wide, however, the mechanisms of disease pathogenesis remain unclear. This study tests the hypothesis that glutathione (GSH) reacts with MDI to form quasistable conjugates, capable of mediating the formation of MDI-conjugated “self” protein antigens, which may participate in pathogenic inflammatory responses. To test this hypothesis, an occupationally relevant dose of MDI (0.1% w/v) was reacted with varying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
58
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(64 citation statements)
references
References 52 publications
6
58
0
Order By: Relevance
“…GSH was reacted with MDI as previously described (Wisnewski, Liu et al 2013). Briefly, 50 µl of 10% (w/v) MDI in acetone from JT Baker (Phillipsburg, NJ) was added dropwise with stirring to 25 ml of 10 mM GSH in 200 mM sodium phosphate, pH 7.4 (final acetone concentration 0.2% v/v).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…GSH was reacted with MDI as previously described (Wisnewski, Liu et al 2013). Briefly, 50 µl of 10% (w/v) MDI in acetone from JT Baker (Phillipsburg, NJ) was added dropwise with stirring to 25 ml of 10 mM GSH in 200 mM sodium phosphate, pH 7.4 (final acetone concentration 0.2% v/v).…”
Section: Methodsmentioning
confidence: 99%
“…Experiments with GSH-MDI were initially performed for 60 minutes at a temperature lower than optimal (e.g. 22°C) as previously described (Sener and Yardimci 2005), since MDI thiocarbamates are more susceptible than aliphatic thiocarbamates to hydrolysis and/or transcarbamoylation reactions at 37°C (Chipinda, Stetson et al 2006, Wisnewski, Liu et al 2013, Wisnewski, Mhike et al 2013). However, subsequent studies at 37°C (data not shown) yielded identical results.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations